Singapore : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper presents a background and recent policy developments for Singapore's financial sector. The paper highlights that in 1968, important tax and regulatory incentives were introduced to attract foreign investment in the financial sector and boost financial sector activity. In particular, the government catalyzed the development of Asian Currency Units (ACUs) by exempting nonresident depositors from withholding tax on ACU deposits. The paper also examines the impact of the external environment on economic activity in Singapore. Competitiveness issues are also discussed.